Prevention of mother-to-child transmission of HIV: the Georgian experience - Tsertsvadze, Tengiz; Kakabadze, Tea; Shermadini, Ketevan; Abutidze, Akaki; Karchava, Marika; Chkhartishvili, Nikoloz; Badridze, Nino; Bokhua, Zaza; Asatiani, Tengiz (Central European Journal of Public Health, 2008)
The objective of this paper is to review experience in prevention of mother-to-child transmission (PMTCT) of HIV in Georgia. BACKGROUND: PMTCT is one of the strategic priorities in Georgia. The first case of HIV infection in pregnant women was reported in 1999. Starting 2005 the National Programme on PMTCT became operational. MATERIALS AND METHODS: One hundred sixteen HIV voluntary counselling and testing (VCT) centers operate throughout the country at antenatal clinics. According to the National PMTCT protocol, all first time attending pregnant women are offered Voluntary Counselling and Testing (VCT). Testing on HIV/AIDS is based on identification of HIV antibodies by screening method and all positive results are referred to the Infectious Diseases, AIDS and Clinical Immunology Research Center (IDACIRC) for the further investigation (confirmation by Western Blot assay) and further management. Data collection was made retrospectively, using information from IDACIRC National HIV/AIDS Data Base, VRF for the period 1999-2007. RESULTS: Prevalence of HIV among pregnant women availing VCT services in 2006 was 0.03%. As of December, 2007 total 69 pregnancies of 64 women were registered at the IDACIRC. Fifty eight women (90.6%) acquired infection through heterosexual contact. None of the HIV positive women reported intravenous injection of illicit drugs. The majority of the HIV infected pregnant women had one sexual partner (90.6%). Of children delivered by 51 positive partners 41(80%) were infected through injecting drugs intravenously and 10 (20%) persons through heterosexual contacts. Throughout the period 1999-2007 14 pregnant women received PMTCT services only partially. In 2 cases children were HIV-infected. In 12 pregnancies women received AZT in about the 28th week of pregnancy. No case of HIV transmission to child was recorded in this group. In 32 cases pregnant women received full prophylaxis therapy and all children were negative for HIV infection. Among 6 pregnant women admitted at IDACIRC later than the 28th week of pregnancy only 1 child was infected. As of December 2007, 5 women are still pregnant. Three of them receive antiretroviral drugs (ARV) prophylaxis with AZT+3TC+SQV/r. Two women are under 28 weeks of gestational age. CONCLUSION: Over the last several years the national response to AIDS in Georgia achieved significant progress. The provision of comprehensive packages of PMTCT services in Georgia has been shown to minimize the risk of vertical transmission. As described above none of the women completing full course of ARV prophylaxis, combined with appropriate infant feeding, transmitted HIV to their children. PMTCT programmes are indisputably the main entry point not only for HIV related care and treatment for women, but also for other comprehensive care and prevention.
Keywords: dospělí; Female; vertikální přenos infekce; novorozenec; Adult; ženské pohlaví; Neonatal Screening; HIV Infections; Adolescent; lidé; Infant, Newborn; těhotenství; HIV infekce; retrospektivní studie; Georgia; revize kvality lékařské péče; Medical Audit; novorozenecký screening; Pregnancy; Retrospective Studies; mladiství; Infectious Disease Transmission, Vertical; Humans